2017
DOI: 10.1039/c7ra02796f
|View full text |Cite
|
Sign up to set email alerts
|

Drug loaded poly(glycerol sebacate) as a local drug delivery system for the treatment of periodontal disease

Abstract: A simple, cost-efficient method to load drugs into poly(glycerol sebacate) polymer. Drugs were able to sustained release for up to 60 days. The drugs loaded polymer showed cytocompatibility and antimicrobial activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…The results matched with those reported by Kim et al on in vitro degradation of PGS in PBS. [58,59] PGS coil compression profile at day 60 of degradation ( Figure 4e) indicated that the load needed to break the coil with radial compression was increased, leading to improved tolerance toward externally applied stress. The change of surface morphology of the coils was also observed from days 0 to 75.…”
Section: Wwwadvancedsciencenewscom Wwwadvtherapcommentioning
confidence: 99%
See 1 more Smart Citation
“…The results matched with those reported by Kim et al on in vitro degradation of PGS in PBS. [58,59] PGS coil compression profile at day 60 of degradation ( Figure 4e) indicated that the load needed to break the coil with radial compression was increased, leading to improved tolerance toward externally applied stress. The change of surface morphology of the coils was also observed from days 0 to 75.…”
Section: Wwwadvancedsciencenewscom Wwwadvtherapcommentioning
confidence: 99%
“…This observation is consistent with literature where it has been well-proven that PGS exhibits minimal swelling. [58,59] PGS coil compression profile at day 60 of degradation ( Figure 4e) indicated that the load needed to break the coil with radial compression was increased, leading to improved tolerance toward externally applied stress. This enhancement could be mainly due to the increase in the porosity and pore size of the PGS structure, which facilitated the enhancement in flexibility of the coils.…”
mentioning
confidence: 99%
“…The PTX/PGSeb nanoparticles showed comparable results to commercial PTX formulations. Yang et al used swelling drug load to charge PGSeb with berberine and chlorhexidine: PGSeb was swelled in ethanol to allow a better diffusion of the drugs and increased permeability [168]. Drug loading had no influence on the mechanical properties of PGSeb (Young's modulus and strain at break) but it did affect the surface wettability.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Direct reaction between dicarboxylic acid and glycerol using typical polyesterification catalysts such as (C 4 H 9 ) 2 SnO, Sn(Oct) 2 , Ti(O t Bu) 4 and Ti(OCH(CH 3 ) 2 ) 4 has been shown to result in hyperbranching . Although this is beneficial when synthesizing elastomers for biomedical applications such as scaffolds for tissue engineering, the lack of control and selectivity does not allow for PPM of the elastomers (to enhance characteristics such as water retention capacity) nor allow synthesis of linear functional polyesters . You et al circumvented this problem in the synthesis of poly(sebacoyl diglyceride) through the use of ring‐opening polymerization rather than direct polycondensation of the monomers (Scheme ) .…”
Section: Chemo‐catalytic Synthesis Of Functional Bio‐based Polymersmentioning
confidence: 99%